Does Culture Influence Asset Managers? Views and Behavior? - Daniela Beckmann; Lukas Menkhoff (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2007)
This research enters new ground by presenting comparative survey evidence on asset managers' views and behavior in the United States, Germany, Japan and Thailand. Relying on Hofstede's four cultural dimensions, we find that cultural differences are most helpful in understanding country differences which cannot be explained by pure economic reasoning. In short, controlling for various determinants, the dimension of more Individualism predicts less herding behavior, more Power Distance leads to older and comparatively less experienced managers in the upper hierarchy, Masculinity brings men into top positions and to higher volumes of assets under personal responsibility, and Uncertainty Avoidance is related to higher safety margins against the tracking error allowed and relatively more research effort. These consequences, i.e. the culturally different importance of herding, age, experience, gender, tracking error and research effort, clearly affect investment behavior, although in a complex way.
Keywords: Z10; G15; G14; G23; 330; Asset Managers; Individualism; Power Distance; Masculinity; Uncertainty Avoidance